2013
DOI: 10.1074/jbc.r112.417857
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Protein N-Glycosylation: New Perspectives and Applications

Abstract: Protein glycosylation is widespread throughout all three domains of life. Bacterial protein N-glycosylation and its application to engineering recombinant glycoproteins continue to be actively studied. Here, we focus on advances made in the last 2 years, including the characterization of novel bacterial N-glycosylation pathways, examination of pathway enzymes and evolution, biological roles of protein modification in the native host, and exploitation of the N-glycosylation pathways to create novel vaccines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
125
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(129 citation statements)
references
References 90 publications
(101 reference statements)
3
125
0
1
Order By: Relevance
“…A majority of the bacterial glycoproteins identified so far are localized at the cell-surface where they are involved in a variety of processes such as biofilm formation, adhesion, cell motility, or immune system escape (2,79,81). In Bacteroides fragilis, a Gram-negative human symbiont, the general O-glycosylation system is involved in the modification of tens of proteins, contributes to in vitro fitness of the species and is also required for the colonization of the mammalian gastrointestinal gut (82,83).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of the bacterial glycoproteins identified so far are localized at the cell-surface where they are involved in a variety of processes such as biofilm formation, adhesion, cell motility, or immune system escape (2,79,81). In Bacteroides fragilis, a Gram-negative human symbiont, the general O-glycosylation system is involved in the modification of tens of proteins, contributes to in vitro fitness of the species and is also required for the colonization of the mammalian gastrointestinal gut (82,83).…”
Section: Discussionmentioning
confidence: 99%
“…Protein glycosylation takes place in bacteria. A considerable amount of information on the biochemical pathways involved in protein glycosylation has been obtained in the genera Campylobacter and Neisseria (1)(2)(3). Hence, functional studies performed on Gram-negative bacteria have revealed important properties of protein glycosylation pathways.…”
mentioning
confidence: 99%
“…Archaea and Eubacteria use their own sets of glycotransferases to assemble distinct oligosaccharides on their unique lipid-phospho carriers (2,11). Consequently, wide diversity is observed in the archaeal and eubacterial N-glycan structures, in terms of the sizes, compositions, branching patterns, and chemical modifications of the constituent monosaccharides (1,12).…”
mentioning
confidence: 99%
“…Such kindThis type of heterogeneity is likely to be present in different organisms of a species also. In one related study, it was established that glycan structures with different chain length are present in the genus Campylobacter when grouped on the basis of thermotolerance [44]. The variation of homologs in different organisms is not surprising since, even among Neisseria, species-and strain-specific polymorphisms have been reported [20,45].…”
Section: Resultsmentioning
confidence: 99%